HIV-associated tuberculous lymphadenitis: the importance of polymerase chain reaction (PCR) as a complementary tool for the diagnosis of tuberculosis - a study of 104 patients Linfadenite tuberculosa associada ao HIV: a importância da reação em cadeia de polimerase (PCR) como ferramenta complementar para o diagnóstico da tuberculose - estudo de 104 pacientes - Marcio Valle Cortez; Cintia Mara Costa de Oliveira; Rossicléia Lins Monte; José Ribamar de Araújo; Bruna Backsmann Braga; Débora Zotteli dos Reis; Luis Carlos de Lima Ferreira; Milton Ozório Moraes; Sinésio Talhari (Sociedade Brasileira de Dermatologia, 2011)
BACKGROUND: Lymphadenitis is common in HIV-positive patients. Diagnosis of the infections associated with this condition is complex, particularly in the case of tuberculosis. Rapid and specific detection of Mycobacterium tuberculosis (M. tuberculosis) is fundamental in ensuring adequate treatment. In addition, frequent causes of lymphadenitis such as those associated with lymphoma and histoplasmosis, among others, must be eliminated as possible causes. OBJECTIVES: To evaluate the accuracy of polymerase chain reaction as a tool for the diagnosis of lymphadenitis resulting from M. tuberculosis. METHODS: In this study, a protocol was developed using the following procedures: direct microscopy using Ziehl-Neelsen staining, culture in Lowenstein-Jensen medium, histology and polymerase chain reaction. RESULTS: A total of 104 patients were included in the study. According to histopathology, 38 patients (36%) were found to have nonspecific chronic lymphadenitis, 27 (26%) had tuberculous lymphadenitis, 11 patients (10.5%) had lymphoma and 9 (8.7%) had histoplasmosis. When Lowenstein-Jensen culture was performed, positive tests for tuberculous lymphadenitis increased by 30%. With polymerase chain reaction, M. tuberculosis DNA was detected in 6 out of 38 samples of non-specific chronic lymphadenitis. Three of these patients were followed up, developed symptoms of tuberculosis and were cured following specific treatment. CONCLUSION: The data obtained in this study suggest that all cases of lymphadenopathies should be submitted to histopathology, Lowenstein-Jensen or Ogawa culture and polymerase chain reaction. Polymerase chain reaction may prove to be useful in providing an early and accurate detection of cases of extrapulmonary tuberculosis in HIV-positive patients with lymphadenopathies, avoiding empirical treatment and the possible development of resistant strains. FUNDAMENTOS: A linfadenite é comum em pacientes HIV-positivos. O diagnóstico das infecções associadas a essa condição é complexo, especialmente em relação à tuberculose. A detecção rápida e específica do Mycobacterium tuberculosis (M. tuberculosis) é essencial para o tratamento adequado. Além disso, frequentes causas de linfadenites tais como as relacionadas a linfoma, histoplasmose, e outras, devem ser afastadas. OBJETIVOS: Avaliar a importância da biópsia cirúrgica excisional das linfadenites e realização dos exames histopatológicos, exames baciloscópicos (Ziehl-Neelsen), cultura (Lowenstein-Jensen) e reação em cadeia da polimerase (PCR) com finalidade diagnostica MÉTODOS: Desenvolveu-se um protocolo para biópsias excisionais de linfonodos, adotando-se os seguintes procedimentos: exame direto de esfregaços corados pelo método de Ziehl-Neelsen, cultura em meio de Lowenstein-Jensen, exame anátomo-patológico e PCR. RESULTADOS: Ao todo foram incluídos 104 pacientes, e o exame histopatológico evidenciou 36% (n = 38 pacientes) de casos de linfadenite crônica inespecífica, 26% (n = 27) de linfadenite tuberculosa, 10,5% (n =11) de linfoma e 8,7% (n = 9) de histoplasmose. Através da cultura no meio de Lowenstein-Jensen, os casos positivos para linfadenite tuberculosa aumentaram para 30%. A PCR detectou M. tuberculosis em 6 das 38 amostras de linfadenite crônica inespecífica. Três desses pacientes foram acompanhados, exibiram sintomas de tuberculose e foram curados após tratamento específico. CONCLUSÃO: Os dados obtidos neste trabalho sugerem que em todos os casos de linfadenopatia deve-se realizar exame histopatológico, cultura em Lowenstein-Jensen ou Ogawa e reação em cadeia da polimerase. A reação em cadeia da polimerase pode ser útil na detecção precoce e acurada de casos de TB extrapulmonar nos pacientes HIV-positivos com linfadenopatias, evitando-se o uso de tratamentos empíricos e o eventual desenvolvimento de cepas resistentes.